A sandwich-like structure composite electrospun membrane of polylactic acid/nano-hydroxyapatite and polyvinyl alcohol/sodium alginate/nano-hydroxyapatite for skull defect repair. (1st November 2021) - Feng, Tianyi; Liang, Bangbang; Bi, Hongyan; Han, Yingchao
Graphical abstract: Highlights: Hydrophilic and hydrophobic bilateral electrospun membrane was well fabricated. The adhesion was greatly improved by optimizing the interface based on sandwich structure. The interface bonding force of composite membrane was improved about 370%. This composite membrane showed great liquid absorption property. This composite membrane showed good biological properties. Abstract: A sandwich-structure like electrospun membrane of polylactic acid (PLA)/nano-hydroxyapatite (nHAP) and polyvinyl alcohol (PVA)/sodium alginate (SA)/nHAP was fabricated for skull defect repair. By controlling the number of repeated AB (A: hydrophobic layer of PLA/nHAP; B: hydrophilic layer of PVA/SA/nHAP) units with a fixed thickness, ABA and BAB sandwich-like structures were constructed to improve the integration of hydrophobic and hydrophilic layers. The results show that the ABA sandwich-like structure played a dominant role in the interface fusion. The tensile strength and interface bonding force were obviously enhanced, which was attributed to the fiber entanglement. Compared to the PLA/nHAP membrane, the composite membrane showed significantly improved water absorption capacity. In vitro and in vivo experiments showed that the composite membrane had good biocompatibility and promoted the repair of skull defects. Therefore, the proposed sandwich-like structure is a feasible strategy to facilitate the adhesion of hydrophobic and hydrophilic fibers in electrospun membranes and to achieve a properly-integrated membrane for tissue defect repair.